Pseudoexfoliation Glaucoma in the National Eye Center, Cicendo Eye Hospital, January–October 2012 - Rizki Fasa Ramdhani; Elsa Gustianty; Fenny Dwiyatnaningrum (Althea Medical Journal, 2015)
Background: Pseudoexfoliation syndrome is characterized by the deposition of a distinctive fibrillar material in the anterior segment of the eye. This condition is a major risk factor for development of glaucoma, termed pseudoexfoliation glaucoma (PEXG). The aim of this study was to describe the characteristic and management of PEXG in the National Eye Center Cicendo Eye Hospital.Methods: A descriptive retrospective study was conducted in October–November 2012 using medical records of PEXG patients in the National Eye Center Cicendo Eye Hospital during January–October 2012. Results: There were 32 patients (43 eyes) diagnosed as PEXG, most of them were male (78.1%), age 70–74 years old (34.4%) and followed by those in the range of age 65–69 years old (21.9%). Most of the cases were unilateral (65.6%) decrease of visual acuity less than 3/60 (76.7%), increase of intraocular pressure (IOP) with majority in the range of 31–40 mmHg (32.6%) and 41–50 mmHg (32.6%), Cup/Disc Ratio 0.9–1.0 (46.51%) and followed by those classified as majority which were hard to assess because of the presence of opaque media (34.89%). The type of glaucoma was open angle glaucoma (88.4%). The treatment received was a combination of two types of antiglaucoma medication and surgery IOPConclusion: PEXG is mostly found in elderly patients. While most of the patients come with high IOP and late stage of the disease IOPKeywords: Characteristics, glaucoma, pseudoexfoliation DOI: 10.15850/amj.v2n1.446